2021
DOI: 10.1109/tdei.2020.009167
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Insulation Materials for DC Cable Insulation — Part I: Space Charge and Conduction

Abstract: Fundamental studies of potential candidates for DC electric power transmission in high temperature environment, including ETFE, FEP, PTFE, PI and PEEK, are carried out and presented in form of the series papers containing space charge and conduction as part I, partial discharge as part II, and the degradation and surface breakdown as part III. In this part, the space charge at 20kV/mm was measured at 25 °C and with a thermal gradient at 50 °C. The electrical conductivity was measured at electric fields ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Over the past decades, the PEA method has witnessed a series of advancements to meet different investigation demands. [114][115][116][117][118][119][120][121] For instance, in order to study the space charge characteristics under elevated temperatures, e.g., ≥100 °C, [122] the poly(vinylidene fluoride-trifluoroethylene)based transducers are replaced by lithium niobite transducers with a high curie temperature ≈1150 °C. In addition, Fukuma developed a fast space charge measurement technique with an interval of 10 µs, which is capable of studying charge carrier dynamics in a short time slot.…”
Section: Acoustic Methodsmentioning
confidence: 99%
“…Over the past decades, the PEA method has witnessed a series of advancements to meet different investigation demands. [114][115][116][117][118][119][120][121] For instance, in order to study the space charge characteristics under elevated temperatures, e.g., ≥100 °C, [122] the poly(vinylidene fluoride-trifluoroethylene)based transducers are replaced by lithium niobite transducers with a high curie temperature ≈1150 °C. In addition, Fukuma developed a fast space charge measurement technique with an interval of 10 µs, which is capable of studying charge carrier dynamics in a short time slot.…”
Section: Acoustic Methodsmentioning
confidence: 99%
“…7, the surface of the sphere covering segment C of DGEBA molecule is concentrated in red, and the surface of the The electron trap depth of the molecule affects the hopping probability of electrons, thus affecting the electron mobility in the transport process and the electrical conductivity of the material. Their relationships are shown in (3), ( 4) and ( 5), where θhop is hopping probability, φt is charge trap depth, k is Boltzmann constant, T is absolute temperature, μ is carrier mobility, μ0 is intrinsic mobility, σ is electrical conductivity, n is electron concentration, q is electron charge quantity, p is hole concentration [12,16] 3) and ( 4) that the hopping probability of the electrons is higher, resulting in a higher electron mobility μn. However, the introduction of the chlorine does not cause a significant change in the hole trap depth, so the hole mobility μp does not change obviously.…”
Section: Effect On the Charge Transportmentioning
confidence: 99%
“…The conductivity of polymer dielectrics depends on the charge transfer rates in the polymer. Studies have shown that the transfer process of space charges in polymer dielectrics is strongly influenced by the distribution of charge traps in polymer molecular chains [3][4][5][6][7][8][9][10][11][12]. When the space charges are transferred to the polymer, they are trapped by deep and shallow traps in the molecular chain [13].…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary factors restricting the development of polymeric insulation for HVDC extruded cables is the space charge accumulation, which distorts the local electric field, accelerates insulation aging and even causes insulation breakdown [3][4][5]. The space charge accumulation poses a greater threat.…”
Section: Introductionmentioning
confidence: 99%